2017
DOI: 10.3171/2016.9.jns161281
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry of the arcuate fasciculus and its impact on language performance of patients with brain tumors in the language-dominant hemisphere

Abstract: OBJECTIVE Cerebral damage in frontal, parietal, and temporal brain areas and, probably more importantly, their interconnections can lead to deficits in language. However, neural plasticity and repair allow the brain to partly compensate for neural injury, mediated by both functional and structural changes. In this study, the authors sought to systematically investigate the relationship between language performance in brain tumor patients and structural perisylvian pathways (i.e., the arcuate fasciculus [AF]) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…It is also possible that the difference in results was impacted by the particular tractography algorithm employed: tensor-based versus HARDI (see Li et al, 2013 andIvanova et al, 2020 on comparing reconstructions of the AF based on different algorithms). In other clinical populations, such as patients with brain tumors in the left hemisphere (Jehna et al, 2017) and children with developmental disorders (Paldino et al, 2016), it has been shown that a smaller AF in the right hemisphere leads to worse language outcomes. Specifically for tumor patients Jehna et al (2017) showed descriptively that patients with fewer language deficits tended to have a symmetric AF or the one lateralized to the right, while those with pronounced language deficits more often had a left-lateralized posterior segment of the AF.…”
Section: Role Of Right Hemisphere Tractsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the difference in results was impacted by the particular tractography algorithm employed: tensor-based versus HARDI (see Li et al, 2013 andIvanova et al, 2020 on comparing reconstructions of the AF based on different algorithms). In other clinical populations, such as patients with brain tumors in the left hemisphere (Jehna et al, 2017) and children with developmental disorders (Paldino et al, 2016), it has been shown that a smaller AF in the right hemisphere leads to worse language outcomes. Specifically for tumor patients Jehna et al (2017) showed descriptively that patients with fewer language deficits tended to have a symmetric AF or the one lateralized to the right, while those with pronounced language deficits more often had a left-lateralized posterior segment of the AF.…”
Section: Role Of Right Hemisphere Tractsmentioning
confidence: 99%
“…In other clinical populations, such as patients with brain tumors in the left hemisphere (Jehna et al, 2017) and children with developmental disorders (Paldino et al, 2016), it has been shown that a smaller AF in the right hemisphere leads to worse language outcomes. Specifically for tumor patients Jehna et al (2017) showed descriptively that patients with fewer language deficits tended to have a symmetric AF or the one lateralized to the right, while those with pronounced language deficits more often had a left-lateralized posterior segment of the AF. Thus, larger AF on the right contributed to better language outcomes, however, only the comparison of the spontaneous speech metric was statistically significant between the two groups differing in AF laterality.…”
Section: Role Of Right Hemisphere Tractsmentioning
confidence: 99%
“…The comorbidity with ADHD implies a single or multiple regional dysfunctions affecting integrated connections between regions. Because of children and adolescents’ cerebral function of differentiation and contingency involved in the neural network, especially when nervous system has been damaged, bypass can be rebuilt to compensate the damaged function called neuroplastic changes (Jehna et al, 2017). Perceptions and mutual influences of a child are more sensitive comparing to that of an adult, and a damaged perception is more likely to influence multisensory integration.…”
Section: Neuroscience Of Adhdmentioning
confidence: 99%
“…To the best of our knowledge, studies involving neurosurgical patients with glioma did not inspect the relation between postoperative reading performance and right AF segment remodeling. Preoperatively, Jehna et al (59) observed that patients with either symmetric or right-lateralized AF segments displayed fewer language deficits than patients with left-sided lateralization. Although these findings could reflect pre-clinical lateralization and are not informative of the effect of surgery on right AF rearrangement, they however corroborate the importance of this contralesional fascicle in preserving language functions, including reading.…”
Section: Study 2: Postoperative Reorganization In Patients With Lggmentioning
confidence: 99%